Factors Associated With Edoxaban Concentration Among Patients With Atrial Fibrillation - Lin, Shin-Yi; Kuo, Ching-Hua; Ho, Li-Ting; Liu, Yen-Bin; Huang, Chih-Fen; Tang, Sung-Chun; Jeng, Jiann-Shing (Frontiers in Pharmacology, 2021)
Background and Purpose: Edoxaban exposure varies across different ethnicities. The purpose of our study was to examine the risk factors associated with high or low edoxaban concentrations in Asian populations. Methods: Participants with atrial fibrillation who were undergoing edoxaban therapy were enrolled. Peak (1–4 hours after edoxaban administration) and trough (24±4 hours from the last edoxaban dose) blood samples were collected to measure edoxaban concentrations using ultrahigh-performance liquid chromatography with tandem mass spectrometry. The edoxaban concentrations were compared to those observed in clinical trials to define a higher- or lower-than-expected range. Multivariate logistic regression was used to analyze the risk factors associated with high or low edoxaban concentrations. Results: Eighty participants (49 men, 61.3%) were enrolled and provided 78 trough and 76 peak samples. Twenty participants (25.6%) were determined to have low trough concentrations, which was associated with higher creatinine clearance and the use of the 30 mg regimen (odds ratio [OR] and 95% confidence interval [CI], 1.06 [1.01, 1.11], p=0.01 and 5.77 [1.34, 24.75], p=0.02, respectively). In contrast, 21 participants (27.6%) had high peak concentrations, which was associated with an off-label overdosing regimen (OR= 4.68 [1.23, 17.70], p=0.02). Conclusions: Our study identified factors associated with increased or decreased edoxaban exposure. The measurement of edoxaban concentration may be recommended for patients with selected characteristics.